Psychiatric and Behavioural Side Effects Associated With Perampanel in Patients With Temporal Lobe Epilepsy. A Real-World Experience - Mammì, Anna; Ferlazzo, Edoardo; Gasparini, Sara; Bova, Valentina; Neri, Sabrina; Labate, Angelo; Mastroianni, Giovanni; Bianco, Concetta Lo; Cianci, Vittoria; Aguglia, Umberto (Frontiers in Neurology, 2022)
Psychiatric and behavioural side effects are common, undesirable effects associated with antiseizure medications use. Temporal lobe epilepsy is the most common focal epilepsy in adults and it is frequently associated with drug resistance. Patients with intractable epilepsy are more likely to have psychiatric and behavioural side effects when taking antiseizure medications and seem to be at higher risk for psychiatric comorbidities. Perampanel is a novel anti-seizure medication approved for focal and generalized epilepsies as add-on therapy. This is a 12-week short-term observational prospective study on people with focal epilepsies consecutively recruited from an Italian tertiary epilepsy centre, aimed to compare incidence and severity of psychiatric and behavioural side effects associated with perampanel use in patients with temporal lobe epilepsy as compared to other focal epilepsies. All patients received add-on perampanel according to indication and clinical judgement. Incidence and severity of psychiatric and behavioural side effects were rated by Neuropsychiatric Inventory Questionnaire. All patients enrolled answered the questionnaire before starting perampanel and after 12 weeks treatment. We found no significant difference in terms of incidence and severity of psychiatric and behavioural side effects associated with perampanel in patients with temporal lobe epilepsy as compared to other focal epilepsies. In line with the literature, the most common adverse effects were “irritability” for both groups and “aggression” for patients with other focal epilepsies.